1997
DOI: 10.1099/00221287-143-3-909
|View full text |Cite
|
Sign up to set email alerts
|

Intraclonal mating in Trypanosoma brucei is associated with out-crossing

Abstract: To examine whether mating can occur within as well as between clones of Trypanosoma brucei, we transformed three T. brucei subspecies stocks with heterologous genes conferring resistance to either hygromycin or Geneticin and carried out a series of inter-and intraclone matings in all possible double drug combinations. Double drug-resistant hybrids were recovered from three of the six out-crosses, but not from any of the three intraclone matings. However, further analysis of cloned progeny trypanosomes from one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 47 publications
(121 reference statements)
0
21
2
Order By: Relevance
“…We infer that meiosis may be a normal part of the trypanosome developmental cycle in the fly, contrary to the traditional narrative that includes only mitotic divisions. In laboratory crosses, mating (and hence meiosis) is considered to occur rarely and only when two different trypanosome strains are present, although low frequencies of intraclonal mating have been detected in both single transmissions and cotransmissions of different strains (32)(33)(34). Even though we observed fluorescence in only a small proportion of trypanosomes at any one time, it remains possible that all SG trypanosomes undergo meiosis at a certain point during establishment of the SG infection.…”
Section: Discussioncontrasting
confidence: 46%
“…We infer that meiosis may be a normal part of the trypanosome developmental cycle in the fly, contrary to the traditional narrative that includes only mitotic divisions. In laboratory crosses, mating (and hence meiosis) is considered to occur rarely and only when two different trypanosome strains are present, although low frequencies of intraclonal mating have been detected in both single transmissions and cotransmissions of different strains (32)(33)(34). Even though we observed fluorescence in only a small proportion of trypanosomes at any one time, it remains possible that all SG trypanosomes undergo meiosis at a certain point during establishment of the SG infection.…”
Section: Discussioncontrasting
confidence: 46%
“…The relationship between these genotypes suggests that they could have originated by self-fertilization; for example, genotype M21, which was first detected in this area in 1959, is heterozygous for alleles at MS42 and 292 could have self-fertilized to produce genotype M4, which is homozygous at both loci, and genotype M5, which is homozygous at minisatellite locus 292 (the major genotype detected between 1988 and 1990). Self-fertilization has been described in T. brucei (15,16). It would appear that for the Busoga (Ugandan) focus at least, human infectivity is associated with one genotype and its predicted self-fertilization products, implying little or no recombination between the human infective and nonhuman infective stocks.…”
Section: Resultsmentioning
confidence: 99%
“…For the experimental cross, flies were infected with a mixture of clones K11 (a GFP TetR transfectant derived from TH2) and T. b. brucei KP2N, a previously transfected derivative of GPAP\CI\82\KP2-I (CLONE 23) (Letch, 1984) carrying the NEO gene in the tubulin gene array (Gibson & Whittington, 1993). Drug-resistant clones of these two parental stocks, TH2 and KP2, were successfully mated in a previous cross (Gibson et al, 1997b …”
Section: Methodsmentioning
confidence: 99%
“…These factors, coupled with the relative inaccessibility of genetic exchange within the tsetse fly vector, have hampered direct observation of the process. After analysis of crosses using selectable drug resistance markers, hybrids were found only in trypanosome populations derived from the salivary glands, not midguts, suggesting that genetic exchange probably takes place in the salivary glands (Gibson & Bailey, 1994;Gibson et al, 1997b). Analysis of the inheritance of genetic markers in hybrid progeny suggests that a meiotic division occurs at some stage Sternberg et al, 1988Sternberg et al, , 1989Gibson, 1989;Turner et al, 1990;Gibson & Stevens, 1999), but triploid hybrids also occur with some frequency Wells et al, 1987;Gibson et al, 1992Gibson et al, , 1997bGibson & Bailey, 1994;Hope et al, 1999) and a haploid life cycle stage has not been found (Shapiro et al, 1984;Tait et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation